MORPHOLOGY AND COMPOSITION FORMATION IN NICKEL SILICON NITRIDE (NI/SI3N4) COMPOSITE LAYERS USING PULSE ELECTRODEPOSITION METHOD: PEMBENTUKAN MORFOLOGI DAN KOMPOSISI PADA LAPISAN KOMPOSIT NICKEL SILICON NITRIDE ( NI/SI3N4 ) MENGGUNAKAN METODE ELEKTRODEPOSISI ARUS PULSA - Irsya Luthfiah Ramadhyagita; Esmar Budi; Teguh Budi Prayitno (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
Metal plating is commonly used in industry to modify surface morphology without altering its original properties. A composite Ni/Si3N4 layer on Tungsten Carbide (WC) was formed using a current density of 0.25 mA/mm2 to analyze the surface morphology and composition of the Ni/Si3N4 composite layer. The formation process employed the pulsed current electrodeposition method at a temperature of 40°C, with a stirring rate of 600 rpm for 1 hour. The solution composition included 0.38 M Ni2SO4·6H2O, 0.17 M Ni2Cl2·6H2O, 0.6 g/L Si3N4, 0.6 g/L SDS (Sodium Dodecyl Sulfate), and 0.49 M H3BO3. The results showed the presence of Ni and Si metal elements with mass compositions of 85.17% and 0.82%, respectively. Surface morphology scanning revealed a smooth surface with slight agglomeration on the substrate.